IDENTIFIKASI MUTU FISIK, KIMIA DAN ORGANOLEPTIK ES KRIM DAGING KULIT MANGGIS (Garcinia mangostana L.) DENGAN VARIASI SUSU KRIM - Nopita Haryanti; Ahmad Zueni (UNIVED Press, Universitas Dehasen Bengkulu, 2015)
Mangosteen is a fruit that is high antioxidant content, especially on the skin. Meat mangosteen skin has a chance to develop into one product is ice cream. Ice cream is a kind of semi-solids with a mixture of milk, sugar, flavors and emulsifiers. This study aims to determine the quality (physical, chemical and organoleptic) ice cream mangosteen rind. Making ice cream in this study includes the preparation of the dough, mixing, shaking, cooking, packaging and freezing agitation. Variation of treatment in this study is mangosteen peel meat : milk cream (100 : 600, 150 : 550, 200 : 500, 250 : 450 and 300 : 400) grams per milliliter. The study design used was completely randomized design (CRD) with five treatments and three replications, if significantly different followed by DMRT. The analysis is done of the overrun , melting speed, the levels of antioxidants and organoleptic (color, flavor and texture). Based on the analysis of physical and chemical quality of the research is on comparative treatment mangosteen peel 300 grams of meat and 400 milliliters of milk cream. While the results of the analysis of organoleptic quality in terms of color, taste and texture of the panelists preferred is the treatment of mangosteen peel 200 grams of meat and 500 grams of milk cream.Keywords : Mangosteen Skin Meat, Milk Cream, Ice Cream